TREATMENT OF VERTIGO- WITH & WITHOUT ANXIOLYTIC DRUG (ALPRAZOLAM 0.25MG) - Ayub, Muhammad Waqas; Bukhari, Syed Muhammad Asad Shabbir; Raza, Mohsin; Waqas, Asma; Khan, Beenish Hassan; Najam, Atif (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare the effect of using the tablet Alprazolam 0.25mg in the treatment outcome of vertigo related anxiety by beck anxiety inventory.Study Design: Comparative study.Place and Duration of Study: Combined Military Hospital Okara Cantt, Sep 2018 to Jun 2020.Methodology: A total of 384 patients were included in the study. They were randomly assigned to group A and B by randomized clinical trial. Group A was given tablet alprazolam 0.25 mg along with the conventional treatment of vertigo and group B was given the treatment of vertigo only and no anxiolytic was added. Their pre & post treatment (after 2 weeks) anxiety level using Beck anxiety inventory was scored.Results: There was a significant improvement in group A patient’s vertigo effects after treatment with alprazolam. Also, it was observed that group A patients responded significant improvement in anxiety score as compared to Group B patients 02 weeks post treatment.Conclusion: Antianxiety treatment should be added in all cases with the conventional treatment of vertigo to reduce the vertigo associated anxiety of the patients.